Development of Variable Speed Drive for Single Phase Induction Motor Based on Frequency Control - Wan Ismail, Ibrahim; Raja Mohd Taufika, Raja Ismail (2011)
The speed of the single-phase induction motor can be controlled by various types of speed control method. In this paper, a system to control the speed of induction motor sing frequency method has been developed and tested. The system was included the PWM control circuit, driver circuit and H- Bridge inverter. The proposed of PWM control circuit is by using LM741 Operational Amplifier, 74AC08 AND logic and SN7404 Hex Inverter. IRF740 MOSFETS was used as switching elements to provide the alternating current to the motor. In this drive, the 12VDC power supply was used for frequency control circuit and driver circuit. While, the 240VDC power supply was used to feed the H-Bridge inverter. The frequency range of the constructed variable speed drive is 16Hz to 56Hz at the constant voltage. PSpice OrCAD simulation software has been used to design and simulate the developed circuits.